2011
DOI: 10.1002/hlca.201000428
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient One‐Pot, Four‐Component Synthesis of {[(1H‐1,2,3‐Triazol‐4‐yl)methoxy]phenyl}‐1H‐pyrazolo[1,2‐b]phthalazine‐5,10‐dione Derivatives

Abstract: The 1-{[(1H-1,2,3-Triazol-4-yl)methoxy]phenyl}-1H-pyrazolo[1,2-b]phthalazine-5,10-dione derivatives 5 were synthesized by a simple and efficient method, i.e., by the four-component, one-pot condensation reaction of phthalohydrazide 4, a (propargyloxy)benzaldehyde 1, an active methylene compound 3 (malononitrile or ethyl cyanoacetate), and an azide 2 in the presence of Cu(OAc) 2 /sodium l-ascorbate as catalyst and 1-methyl-1H-imidazolium trifluoroacetate ([Hmim](CF 3 COO)) as an ionicliquid medium in good to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…[164] The ionic liquid was employed in catalytic amounts and a solvent-free protocol of this strategy could be realized. [165] Just recently, upon employing dimedone and 1,3-cyclohexanedione as active methylene compounds, the cyclocondensation-CuAAC sequence gave rise to the formation [(1,2,3-triazol-4-yl)methoxy-phenyl]-2H-indazolo [2,1b]phthalazinetriones 94 in a one-pot fashion (Scheme 70). Later, the same group showed that 1-{[(1H-1,2,3t-4-yl)methoxy]phenyl}-1H-pyrazolo [1,2b]phthalazine-5,10-diones 93 were accessible by a four-component synthesis employing the same catalyst system (Scheme 69).…”
Section: Multiple Mcrs Coupled With Cuaacmentioning
confidence: 99%
See 1 more Smart Citation
“…[164] The ionic liquid was employed in catalytic amounts and a solvent-free protocol of this strategy could be realized. [165] Just recently, upon employing dimedone and 1,3-cyclohexanedione as active methylene compounds, the cyclocondensation-CuAAC sequence gave rise to the formation [(1,2,3-triazol-4-yl)methoxy-phenyl]-2H-indazolo [2,1b]phthalazinetriones 94 in a one-pot fashion (Scheme 70). Later, the same group showed that 1-{[(1H-1,2,3t-4-yl)methoxy]phenyl}-1H-pyrazolo [1,2b]phthalazine-5,10-diones 93 were accessible by a four-component synthesis employing the same catalyst system (Scheme 69).…”
Section: Multiple Mcrs Coupled With Cuaacmentioning
confidence: 99%
“…A variety of substrates with both electron‐withdrawing and electron‐donating propensity were well tolerated. Later, the same group showed that 1‐{[(1 H ‐1,2,3t‐4‐yl)methoxy]phenyl}‐1 H ‐pyrazolo[1,2‐ b ]phthalazine‐5,10‐diones 93 were accessible by a four‐component synthesis employing the same catalyst system (Scheme ) 165. Just recently, upon employing dimedone and 1,3‐cyclohexanedione as active methylene compounds, the cyclocondensation‐CuAAC sequence gave rise to the formation [(1,2,3‐triazol‐4‐yl)methoxy‐phenyl]‐2 H ‐indazolo[2,1‐ b ]phthalazinetriones 94 in a one‐pot fashion (Scheme ) 166.…”
Section: Multiple Mcrs Coupled With Cuaacmentioning
confidence: 99%
“…The copper‐catalyzed 1,3‐dipolar cycloaddition of an azide to a terminal alkyne is an easy route to tolerate a wide diversity of functional groups. The CuAAC reaction gives excellent yields and has been applied in organic synthesis, materials science, catalysis, and the biochemistry …”
Section: Introductionmentioning
confidence: 99%
“…13 Recently, the four-component synthesis of 1H-pyrazolo[1,2-b]phthalazine-5,10-dione derivatives has also been reported. [14][15][16][17][18][19] However, these methodologies exhibit at least one of the following disadvantages: environmentally harmful solvents, expensive reagents, sensitive catalysts, cumbersome preparation process for the required catalyst or tedious workup conditions. Nevertheless, the development of efficient and practical catalysts for the preparation of 1H-pyrazolo[1,2-b]phthalazine-5,10-dione derivatives is of importance.…”
mentioning
confidence: 99%
“…The products are known and their structures were characterised by comparing their physical and spectral data with those of authentic samples. [8][9][10][11][12][13][14][15][16][17][18][19] Note that all the products were purified by a simple process of crystallisation and filtration; no chromatography was involved.…”
mentioning
confidence: 99%